Effect of photodynamic therapy on the mechanical properties and bond strength of glass-fiber posts to endodontically treated intraradicular dentin - Strazzi Sahyon, Henrico Badaoui [UNESP]; Silva, Paloma Pereira da [UNESP]; Oliveira, Murilo Silva de [UNESP]; Cintra, Luciano Tavares Angelo [UNESP]; Gomes Filho, João Eduardo [UNESP]; Santos, Paulo Henrique dos [UNESP]; Araújo, Gustavo Sivieri de [UNESP] (Elsevier B.V., 2018)
Statement of problem. The use of photosensitizers in photodynamic therapy promotes intraradicular microbial reduction during nonsurgical endodontic therapy. However, studies are lacking on the consequences of the application of these agents on the mechanical properties of intraradicular dentin and on the bond strength of glass-fiber posts. Purpose. The purpose of this in vitro study was to evaluate the influence of photodynamic therapy on the bond strength of glass-fiber posts using a push-out test and, additionally, to measure the Martens hardness (MH) and elastic indentation modulus (Eit) of intraradicular dentin when different photosensitizers are used. Material and methods. Eighty bovine teeth were used to simulate experimental endodontic treatments. Biomechanical instrumentation was performed for all root canals, and the teeth were distributed into 5 groups: control-deionized water; methylene blue 50 mg/L + red laser; methylene blue 100 mg/L + red laser; curcumin 500 mg/L + blue LED; and curcumin 1000 mg/L + blue LED. The MH and Eit of intraradicular dentin were measured using an ultramicrohardness tester under a load of 3 mN (n=8). The push-out bond strength of glass-fiber posts to dentin was measured using a universal testing machine (n=8). Mechanical properties and bond strength data were subjected to the Kruskal-Wallis test, ANOVA, and Fisher least significant difference test (alpha=.05). Images of representative specimens were obtained using a scanning electron microscope. Results. The MH, Eit, and bond strength of intraradicular dentin were influenced by the photo-sensitizer used. In general, curcumin promoted lower mechanical properties values but higher bond strength values. Conclusions. Photosensitizers influenced the mechanical properties of intraradicular dentin and the bond strength of glass-fiber posts, and methylene blue at 50 mg/L had no marked effect on the mechanical properties of the dentin or the bond strength values.